RESOURCE-SAVING TECHNOLOGY OF PRODUCTION OF ZINC ANODES FOR BRASS-PLATING OF STEEL CORD - E. I. Marukovich; E. F. Baranovskij; G. P. Korotkin; Ju. V. Petrunja (Литьë и металлургия)
In the article there are examined the questions of optimization by means of mathematic modeling of the processes of blending and mixing of ceramic sialon powders, as particles sizes, their allocation and composition determine solidity and efficiency of ceramics.